Lower limb work-energy patterns in elite race walking - Hanley, B.; Bissas, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Race walking is part of the athletics programme at the Olympic Games and all other major athletics championships. Despite this high profile, no research has measured the amount of work done at the major lower limb joints, and such data might be particularly informative in this unique form of gait given its distinctive rules. The aim of this study was to measure the work done in each of the main leg joints in elite race walkers. Methods: Ten elite male race walkers (stature: 1.79 m (± 0.06); mass: 67.0 kg (± 9.4)) and 10 elite female race walkers (stature: 1.69 m (± 0.05); mass: 53.9 kg (± 5.6)) participated in the study; in total, 10 had competed at the Olympic Games. They performed multiple trials, and ground reaction forces (Kistler, Winterthur) were recorded of the contact phase (1000 Hz) and synchronised with high-speed videography (100 Hz) (RedLake, San Diego). Sagittal plane joint powers at the hip, knee and ankle were calculated from the force and video data; the amount of work done at each joint was calculated as the time integral of the power curve using the trapezoidal rule. Results: Overall, the lower limb was a net generator of energy (16.0 ± 9.8 J), with most positive work done during stance (19.3 ± 11.0 J). The ankle was a net generator of energy, with most of this work occurring during stance (7.7 ± 5.2 J). The hip was also a net generator of energy, but with more positive work done during swing (41.4 ± 12.0 J) than during stance (15.2 ± 10.2 J). By contrast, the knee was a net dissipater of energy (-50.0 ± 12.7 J), with large negative work values occurring during swing (-46.4 ± 9.5 J). This led to a mean net dissipation of energy in the lower limb during swing (-3.2 ± 8.9 J). The main muscle groups that did positive work were the hip extensors (42.3 ± 10.1 J), hip flexors (22.4 ± 7.1 J) and ankle plantarflexors (16.4 ± 3.8 J). Most of the negative work was done by the knee flexors (-38.2 ± 7.1 J) and knee extensors (-18.7 ± 6.4 J). Discussion: The hip extensors did most of the positive work during the gait cycle and emphasised their central function in elite race walking; the hip flexors were important in late stance / early swing to drive the thigh forwards, and the extensors important in late swing / early stance in preventing too much braking at initial contact. By contrast, the amount of work done by the knee during stance was minimal, and in effect, the straightened knee rule restricted the leg to the role of a rigid lever around which the body rotated because of the forward momentum of the contralateral swing leg. The key points for coaches are that the strength and endurance of the hip muscles must be well developed for elite race walking performances, and the frequent injuries to the hamstrings in race walking are most probably due to the considerable negative work done by the knee muscles during late swing.